The Influence of Profitability Against Corporate Value With Capital Structure As Mediation Variables on Agricultural Sector Companies on the Indonesia’s Stock Exchange - Simatupang, Limson; Wijaya, Errin Yani; ', Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the effect of profitability and capital structure partially to the corporate value, to determine the effect of profitability and capital structure simultaneously to the corporate value and to determine the indirect effect of profitability to the corporate value through capital structure. The study population was the entire agricultural sector companies listed in Indonesia Stock Exchange 2009-2012. The population consists of 4 sectors, namely plantations, the livestock sector, fisheries sector, and other sectors. From the four sectors, sample is used in this research consists of 17 companies listed on the Indonesia Stock Exchange in 2009-2012. Samples obtained by purposive sampling to select a sample with certain criteria, so in accordance with research design. To analyse the data using path analysis. The results of this study stated that the profitability has negative effect and a significant on capital structure and have direct influence of 0.1429 or 14.29% . Capital Structure has a significant effect on Corporate Value and have direct influence of 0.2266 or 22.66%. Profitability has no significant effect on the corporate value and have a direct influence at 0.0198 or 1.98%. Profitability has a significant effect to the capital structure, but Profitability has no effect on corporate value, thus the Profitability is not directly influence the corporate value. Profitability will effect the value of the company if it is mediated by the capital structure with the indirect effect of 0.1799 or 17.99%.Keywords: Debt to Equity Ratio, Return on Investment, Corporate Value